The complete nucleotide sequence of the mitochondrial genome of the Oriental Pieris, Pieris canidia (Lepidoptera: pieridae). (1st November 2016) - Fang, Jie; Wu, Yunhe; Wang, Hui; Sun, Zhonglou; Han, Demin; Zhang, Baowei
Abstract: The complete mitochondrial genome of Pieris canidia was investigated and analyzed. The mitochondrial genome is a circular molecule of 15, 153 bp, containing 13 protein-coding genes (PCGs), 2 rRNA genes, 22 tRNA genes and an A+T-rich region. The nucleotide composition of the P. canidia mitogenome is strongly biased toward A+T nucleotides (79.66%). Nine protein-coding genes and 14 tRNA genes are encoded on the H strand, and the other 4 protein-coding genes and 8 tRNA genes are encoded on the L strand. The arrangement of genes is identical to all know the genus Pieris species.